2002
DOI: 10.1002/em.10109
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage in cytologically normal urothelial cells of patients with a history of urothelial cell carcinoma

Abstract: In order to determine if patients with a history of previous urothelial cell carcinoma (UCC) but with current normal urinary cytology have DNA damage in urothelial cells, the single-cell gel electrophoresis (comet) assay was conducted with cells obtained by urinary bladder washings from 44 patients (28 with a history of previous UCC). Increased DNA damage was observed in cytologically "normal" urothelial cells of patients with a history of UCC when compared with referents with no similar history and after corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
7
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
5
7
1
Order By: Relevance
“…These findings strengthen the notion that MN scoring could be used in cytopathological analyses to assist in the proper diagnosis of these cases [10]. We have previously shown that genetic instability could be detected in urothelial cells, even before cellular atypia was detectable by cytology [13]. In this previous study, increased MNC frequencies were observed in normal urothelial cells obtained from bladder washings of patients with a history of UCC and/or smoking, but this increase was not statistically significant when compared to urothelial cells from a control population, which was likely due to the relatively small sample size [13].…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings strengthen the notion that MN scoring could be used in cytopathological analyses to assist in the proper diagnosis of these cases [10]. We have previously shown that genetic instability could be detected in urothelial cells, even before cellular atypia was detectable by cytology [13]. In this previous study, increased MNC frequencies were observed in normal urothelial cells obtained from bladder washings of patients with a history of UCC and/or smoking, but this increase was not statistically significant when compared to urothelial cells from a control population, which was likely due to the relatively small sample size [13].…”
Section: Introductionsupporting
confidence: 82%
“…The micronuclei (MN) frequency is a widely used biomarker for chromosome instability [8][13]. MN are chromosome fragments or whole chromosomes that are not incorporated into daughter nuclei during cell division [8], and the frequency of micronucleated cells (MNC) may predict cancer risk, suggesting that increased MN formation may be associated with early carcinogenic events [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liquid obtained from the bladder washing (total of 15 ml) was divided into two aliquots: one (5 ml) was used for routine urinary cytology and other for the comet assay. 3,12 Cell viability was evaluated by trypan blue exclusion. After centrifugation of the second aliquot (for comet assay), the cell pellet (approximately 5 ϫ 10 5 cells) was embedded in low-melting point agarose (0.5%), layered onto a microscope slide precoated with agarose, allowed to solidify at 4 C, and lysed for 24 hour at 4 C in a solution containing 2.5 M NaCl, 100 mM Na 2 ethylenediaminetetraacetic acid, 10 mM Tris, pH 10, 2% sodium sarcosinate with 1% Triton X-100, and 10% dimethyl sulfoxide added just before use.…”
mentioning
confidence: 99%
“…5 Increased DNA damage, as detected by the comet assay, has been shown in the urothelial cells of human patients at increased risk for urothelial cell carcinoma, such as smokers 5 and patients with a history of urothelial cell carcinoma but with normal-looking cytology. 3 We are unaware of prospective studies in the literature evaluating primary DNA damage as a potential risk factor for cancer. The biologic significance of primary DNA damage in viable cells is the risk for mutation accumulation and its relationship with genomic instability in vitro 6 and in vivo.…”
mentioning
confidence: 99%